2011
DOI: 10.1007/s10529-011-0745-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the citrinin biosynthetic gene cluster from Monascus aurantiacus

Abstract: Monascus aurantiacus produces high amounts of citrinin which is a mycotoxin with nephrotoxic activity. Six putative citrinin biosynthesis genes have been discovered in M. purpureus and at least 10 genes are responsible for its biosynthesis. However, the sequence of citrinin pathway gene cluster in M. aurantiacus has not been reported. Here, the putative sequence of citrinin biosynthetic gene cluster was obtained by a PCR-based strategy for screening a genome fosmid library of M. aurantiacus. A sequence of 43 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 15 publications
(19 reference statements)
0
45
0
Order By: Relevance
“…The blockage of the citrinin biosynthesis pathway would result in a reduction in citrinin production and an improvement of red pigments. 11,16 However, our results suggested that the biosynthesis of citrinin is independent of that of the pigments because the red pigments did not increase when the ctnB gene was disrupted. One could probably speculate that Monascus does not share enzymes responsible for citrinin biosynthesis and pigment synthesis, despite the same precursor.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 73%
“…The blockage of the citrinin biosynthesis pathway would result in a reduction in citrinin production and an improvement of red pigments. 11,16 However, our results suggested that the biosynthesis of citrinin is independent of that of the pigments because the red pigments did not increase when the ctnB gene was disrupted. One could probably speculate that Monascus does not share enzymes responsible for citrinin biosynthesis and pigment synthesis, despite the same precursor.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 73%
“…[21] Overexpression of this pathway (Figure 3b)a lso led to the isolation of the protein tyrosine kinase inhibitors paeciloquinone A( 7 )a nd B( 8 ; Figures S33 and S34), which are shunt products of the biosynthetic pathway of 6 (Scheme S2). [23] The DhdaA strain produced three labdane-related diterpenoid compounds (9-11)a sc haracterized by NMR spectroscopy (Table S14, Figures S35-S44). [23] The DhdaA strain produced three labdane-related diterpenoid compounds (9-11)a sc haracterized by NMR spectroscopy (Table S14, Figures S35-S44).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The gene cluster spanned a 21 kb region containing 6 genes, including pksCT, ctnA genes, containing 10 new genes besides the above 6 genes, but the functions of only a few genes have been analyzed and predicted, and most genes in the citrinin biosynthetic gene cluster are still not investigated (Li et al 2012). Therefore, it still needs so much effort to study the biosynthesis pathway of citrinin.…”
Section: Introductionmentioning
confidence: 99%